Breast Cancer Risk Among Male BRCA1 and BRCA2 Mutation Carriers - Tai, Yu Chuan (2007)
Men who carry germline mutations in the BRCA2 gene have a higher risk of developing breast carcinoma than men in the general population. Men who carry germline mutations in the BRCA1 gene may also be at a higher risk for breast carcinoma, but this association is not as well established. We evaluated the risks of developing breast carcinoma for male BRCA1 and BRCA2 mutation carriers in the US population based on data from 1939 families with 97 male subjects with breast carcinoma that were collected from eight centers across the National Cancer Institute’s Cancer Genetics Network. At all ages, the cumulative risks of male breast cancer were higher in both BRCA1 and BRCA2 mutation carriers than in noncarriers. The relative risks of developing breast cancer were highest for men in their 30s and 40s and decreased with increasing age. Both the relative and cumulative risks were higher for BRCA2 mutation carriers than for BRCA1 mutation carriers. The estimated cumulative risk of breast carcinoma for male BRCA1 mutation carriers at age 70 years was 1.2% (95% confidence interval [CI] = 0.22% to 2.8%) and for BRCA2 mutation carriers, 6.8% (95% CI = 3.2% to 12%).